Temperature Control of Induction Heating Using a Multi Coil Solution - Watsfeldt,Elias; Åsljung,Andreas (2020)
In induction heating processes with complex workpiece geometries or stringent requirements, more than one induction coil is usually needed to obtain acceptable results. One objective could be to achieve uniform heating, with minimal temperature variations throughout the workpiece. One frequency converter for each induction coil could be used, but it would not be cost-effective, and instead, it is desired only to use one frequency converter for multiple coils. To be able to control multiple coils from one frequency converter, the resonance frequencies of the coils need to be distributed appropriately. The frequency placement happens with a choice of capacitor value from a set of given values. The project assumes already designed coils, and the first part of the thesis aims to find the optimal selection of capacitors, given a set of coils. The latter is to find a suitable control strategy given the optimal capacitor selection. One of the main issues that limit multi-coil placement are the harmonics of the frequency converter’s square wave. Care has to be taken not to place the resonance frequencies where the harmonics unintentionally excite the wrong coils. The system also imposes several limitations and requirements, such as soft switching of transistors and current and voltage specification of components. A program was written to find the best set of capacitor values for a combination of coils and evaluate the established criteria to find the optimal resonance frequency placement. The program outputs a frequency interval for each coil that confides with system limitations and criteria. Frequencies within these intervals can then be used for temperature control of the process. Multiple strategies are proposed, but only one is implemented and tested. The implemented strategy stems from the idea that at every control loop, heat the zone furthest away from its reference a certain amount of degrees, then repeat. This strategy shows promise but would be unsuitable in some cases where high load disturbances exist, in which case the other more complicated strategies would be needed.